2013
DOI: 10.1097/wnr.0b013e328361315e
|View full text |Cite
|
Sign up to set email alerts
|

Altered semantic integration in autism beyond language

Abstract: Autism spectrum disorders (ASDs) are characterized by impaired communication, particularly pragmatic and semantic language, resulting in verbal comprehension deficits. Semantic processing in these conditions has been studied extensively, but mostly limited only to linguistic material. Emerging evidence, however, suggests that semantic integration deficits may extend beyond the verbal domain. Here, we explored cross-modal semantic integration using visual targets preceded by musical and linguistic cues. Particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The less IFG activation found in ASD youths during retrieval/selection of semantic knowledge (Chen, Gau, Lee, & Chou, 2016) suggests that they show the lower engagement of mechanisms involved in cognitive control required for higher-level comprehension. Event-related potentials (ERP) research demonstrates that the N400 effect important for semantic integration is reduced or absent during lexicosemantic processing in individuals with ASD compared to TD individuals, reflecting an impairment at the word and the sentence level understanding (Coderre, Chernenok, Gordon, & Ledoux, 2017;Megnin et al, 2012;Ribeiro, Valasek, Minati, & Boggio, 2013). Previous studies have shown that adults with ASD have impairments for both linguistic and visual narrative comprehension, suggesting that they have deficits in integrating contextual information (Coderre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The less IFG activation found in ASD youths during retrieval/selection of semantic knowledge (Chen, Gau, Lee, & Chou, 2016) suggests that they show the lower engagement of mechanisms involved in cognitive control required for higher-level comprehension. Event-related potentials (ERP) research demonstrates that the N400 effect important for semantic integration is reduced or absent during lexicosemantic processing in individuals with ASD compared to TD individuals, reflecting an impairment at the word and the sentence level understanding (Coderre, Chernenok, Gordon, & Ledoux, 2017;Megnin et al, 2012;Ribeiro, Valasek, Minati, & Boggio, 2013). Previous studies have shown that adults with ASD have impairments for both linguistic and visual narrative comprehension, suggesting that they have deficits in integrating contextual information (Coderre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have found altered, but not absent semantic processing in individuals with ASD. Ribeiro et al (2013) investigated semantic processing in seven children with high functioning autism, using a semantic congruency sentence task. They found that there was no N400 response in the children with ASD, but instead the conditions were differentiated by a late positive potential (LPP).…”
Section: Introductionmentioning
confidence: 99%
“…A likely candidate is therefore a deficit of lexical/semantic memory, consistent with claims for low-functioning autism [ 56 ]. As well, studies of adults with autism using event-related potentials consistently report abnormalities of the N400 component [ 77 , 78 ], consistent with semantic memory dysfunction (on the interpretation of the N400 that it indexes semantic memory [ 55 ]). However, as performance with single words can be quite good in individuals with autism, and even better-than-normal in some respects [ 41 , 79 , 80 ], it may be that, at least in high-functioning autism, an idiom deficit reflects only certain aspects of semantic memory that are deficient in the disorder.…”
Section: Discussionmentioning
confidence: 86%